Feasibility Study of Web-Based Internship’s Information System Based on ISO 1926 Standard - Alifah, Nurul Lailani; Wihidayat, Endar Suprih; Sujana, Yudianto (IJIE (Indonesian Journal of Informatics Education), 2019)
At this globalization era, unlimited accessible information across the overseas, increasing competition for getting a job. This condition affected a university student to enhance their skills to keep competitive. One method to improve is conducting an internship program (PI) at industrial companies. Thus, to implement and monitor the program, Informatics and Computer Engineering for Education Department (PTIK) at Universitas Sebelas Maret was used a web-based information system. This research aims to conduct and analyze a feasibility study of PI information system built for PTIK based on ISO 9126 standard. The research has two phases, the first is developing the system using waterfall method, and the second is feasibility study based on five characteristics of ISO 9126 standard which is:  (1) functionality, (2) reliability, (3) usability, (4) maintainability, and (5) portability. Eighteen PI information system examiners are involved. Those reviewers divided into three categories:  system’s expert, substance’s expert, and the end user of the PI information system. Examining result shows that the average number of all categories is 85.5%. It means that PI information system considered as very-feasible to implement and use.